(untitled) (University Journal of Zoology, Rajshahi University, 2009)
The prevalence of intestinal parasitic infestation and anaemic status of adolescent boys (age 10-19 years) of two selected villages, Kutumbopur, Comilla and Gazirchat, Dhaka districts was investigated. Anaemic status was determined by measuring hemoglobin percentage and parasitic infestation was detected and identified under microscope with wet mount and stained preparations. Out of 106 adolescent boys, only two (1.9%) showed severe anaemia. Among the other anaemic status, 50.9% was moderately anaemic, 39.6% mildly anaemic and 7.5% non anaemic. Adolescent boys were infected (49.01%) with one or more type of protozoan and helminth parasites. Both anaemia and parasitic infestation were more prevalent in Gazirchat while compared to Kutumbopur. Parasitic infestation and anaemia was not correlated. Key words: Anaemia, adolescent boys, Ascaris, Trichuris, Entamoeba, Giardia Â doi:10.3329/ujzru.v27i0.1957 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 63-65